From Computer-Assisted Language Learning (CALL) to Augmented Reality (AR): Technological Interventions in Bilingual Language Learning - Abdur Rahman (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2025)
Bilingual education is a critical component of modern educational practices, aimed at fostering bilingualism and improving academic success. Technology-enhanced language learning (TELL) has emerged as a transformative tool in this domain. This paper explores TELL's impact on bilingual education by synthesising theoretical frameworks, examining diverse technologies, evaluating effectiveness, and addressing implementation challenges. The theoretical foundations include constructivism, sociocultural theory, and cognitive load theory. Constructivism highlights the active construction of knowledge through interactive technology-based environments, while sociocultural theory emphasises collaboration and cultural exchange. Cognitive load theory guides the efficient design of TELL materials to enhance learning outcomes. Technologies such as computer-assisted language learning (CALL), mobile apps, virtual reality (VR), augmented reality (AR), and online collaboration tools are instrumental in TELL. These platforms offer personalised learning experiences, immersive environments, and opportunities for synchronous and asynchronous interactions, significantly improving language proficiency, cultural understanding, and overall educational outcomes. Despite its potential, challenges like limited access to technology, varying digital literacy levels, and the need for teacher training hinder widespread adoption. Addressing these obstacles requires promoting equitable access, enhancing digital skills, and providing professional development for educators. Future research should prioritise innovative TELL approaches, long-term evaluations, and best practices for effective integration into bilingual education. By influencing technology and theoretical insights, TELL has the potential to revolutionise bilingual education, fostering interactive, engaging, and culturally enriched learning experiences while empowering global citizens in a digital age.